The Influence of CoO/P2O5 Substitutions on the Structural, Mechanical, and Radiation Shielding of Boro-Phosphate Glasses - Ahmed M. A. Mostafa (MDPI AG, 2021)
A new glass system (50−x)P2O5–20B2O3–5Al2O3–25Na2O–xCoO was manufactured using a standard melt quenching procedure, where 1≤ x ≤ 12 mol%. The characteristics of boro-phosphate-glasses containing CoO have been studied. The effect of CoO on the radiation-protective properties of glasses was established. The density of the prepared glasses as a function of CoO increased. XRD was used to check the vitreous structure of samples. Fourier-transform infrared (FTIR) spectroscopy was used to study the structure of each sample. FTIR demonstrated that connections grew as CoO/P2O5 levels increased, and the FTIR spectra shifted to higher wavenumbers. The increment of CoO converts non-bridging oxygens associated with phosphate structural units into bridging oxygens. This process increases the concentration of BO4 structural units and creates new, strong and stable bonds B–O–P, i.e., there is polymerization of the boro-phosphate glass network. With an increase in the ratio of CoO/P2O5 in the produced samples, ultrasonic velocities and elastic moduli were observed to increase. The coefficients of linear and mass attenuation, the transmittance of photons in relation to the photon energy, the efficiency of radiation protection in relation to the photon energy, and the thickness of the absorber were modeled using these two methods (experimental and theoretical). From the obtained values, it can be concluded that the 12Co sample containing 12 mol% will play the most influential role in radiation protection. An increase in the content of cobalt-I oxide led to a significant increase in the linear and mass attenuation coefficient values, which directly contributes to the development of the radiation-protective properties of glass.